2007
DOI: 10.1007/s10344-007-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Lead concentrations and lead and strontium stable-isotope ratios in teeth of European roe deer (Capreolus capreolus)

Abstract: The study reports lead concentrations and lead and strontium stable-isotope ratios in mandibular molars of roe deer from three different areas in western Germany. Lead concentrations in third molars ranged between 0.23 and 36.61 µg/g (dry weight). Comparing lead concentrations in first molars and third molars in a group of ca. 1.5-or ca. 2.5-year-old individuals from the same area revealed an effect of tooth age on tooth lead content. The higher lead concentrations in the first molars were attributed to the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…It is the purpose, here, to shed light on what materials would be best to use in this regard, given that there is no consensus at all in the current literature in this regard. (Kierdorf et al, 2008), as some deer have relatively small roaming ranges of less than 70-80 ha . Chemical compositions of deer teeth have also been used to monitor environmental pollution Richter et al, 2011).…”
Section: Geological Vs Biological-available Srmentioning
confidence: 99%
“…It is the purpose, here, to shed light on what materials would be best to use in this regard, given that there is no consensus at all in the current literature in this regard. (Kierdorf et al, 2008), as some deer have relatively small roaming ranges of less than 70-80 ha . Chemical compositions of deer teeth have also been used to monitor environmental pollution Richter et al, 2011).…”
Section: Geological Vs Biological-available Srmentioning
confidence: 99%
“…Other studies have analyzed nonhuman teeth to assess lead exposure and demonstrated that the animal species teeth are well suited as a bio-indicator for assessing lead contamination of the environment [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in precise isotope ratios is constantly increasing and spreading from its traditional applications in geochemistry (e.g. dating 1,2 ) and archaeology 3,4 to other areas including provenance studies 5 and isotope tracing in nutritional surveys [6][7][8] and in clinical trials. The sensitivity, acquisition speed, high sample throughput and pseudo-high resolution capability of multicollector inductively coupled plasma mass spectrometers (MC-ICPMS) have caused the number of publications to leap since the millennium.…”
Section: Introductionmentioning
confidence: 99%